Bibliometric Structure of Collective Identities : Progress of Publication on Collective Identity in the Scopus Database - Mohamad Naim, Hafizan; Mohd Sani, Mohd Azizuddin (Advances in Humanities and Contemporary Studies, 2023)
The formation of collective identity, at its core, is the product of people navigating through social relations. Collective identity has become one of the most prominent sub-theories in social identity theory. This study examines the progress of publication on collective identity and mapping the structure of its bibliometric information on journals published in the Scopus database. The online retrieval process was done on 28 July 2020 and obtained 689 documents. The data were analysed using a standard bibliometric approach using Microsoft Excel, VOSviewer, and Harzing’s Publish and Perish. The result shows an increased growth rate of literature in the year 1997. The growth particularly linked to the publication of “Who Is This “We”? Levels of Collective Identity and Self Representations” by M.B. Brewer and W. Gardner’ in 1996 and “The Construction of Collective Identity.”S.N. Eisenstadt, B. Giesen in 1995. This study reveals research on collective identity subject are predominantly related to constructive analysis, identity analysis, discourse analysis, and collective action analysis. There is increased attention in linking social media with collective identity research, while the social movement domain will continue to be an important domain within the corpus. This study offers an insight to researchers on current trends and the future trajectory of collective identity research.